Conformational characterization of human eukaryotic initiation factor 2 alpha: a single tryptophan protein - Sreejith, R. K.; Yadav, Viveka Nand; Varshney, Nishant K.; Berwal, Sunil K.; Suresh, C. G.; Gaikwad, Sushama M.; Pal, Jayanta K. (Biochemical and Biophysical Research Communications, 2009)
The alpha-subunit of the human eukaryotic initiation factor 2 (heIF2 alpha), a GTP binding protein, plays a major role in the initiation of protein synthesis. During various cytoplasmic stresses, eIF2 alpha gets phosphorylated by eIF2 alpha-specific kinases resulting in inhibition of protein synthesis. The cloned and over expressed heIF2 alpha, a protein with a single tryptophan (trp) residue was examined for its conformational characteristics using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The steady-state fluorescence spectrum, fluorescence lifetimes (tau(1) = 1.13 ns and tau(2) = 4.74 ns) and solute quenching studies revealed the presence of trp conformers in hydrophobic and differential polar environment at any given time. Estimation of the alpha-helix and beta-sheet content showed: (i) more compact structure at pH 2.0, (ii) distorted alpha-helix and rearranged beta-sheet in presence of 4 M guanidine hydrochloride and (iii) retention of more than 50% ordered structure at 95 degrees C. Hydrophobic dye binding to the protein with loosened tertiary structure was observed at pH 2.0 indicating the existence of a molten globule-like structure. These observations indicate the inherent structural stability of the protein under various denaturing conditions. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Circular dichroism; heIF2 alpha; K562 cells; Molten globule; Steady-state and time-resolved fluorescence